2018
DOI: 10.1128/jvi.00600-18
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus Infection Induces both eIF2α Phosphorylation-Dependent and -Independent Host Translation Shutoff

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is an that has caused tremendous economic losses in the global swine industry since it was discovered in the late 1980s. Inducing host translation shutoff is a strategy used by many viruses to optimize their replication and spread. Here, we demonstrate that PRRSV infection causes host translation suppression, which is strongly dependent on viral replication. By screening PRRSV-encoded nonstructural proteins (nsps), we found that nsp2 participates in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 85 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…This downregulation of IFITM proteins has already been shown to promote influenza virus A infection in HeLa cells and HFFs [180]. Interestingly, viruses employing internal ribosome entry sites (IRESs) for translation of their mRNAs may benefit from the inhibition of mTORC1, since those viruses do not depend on mTOR-driven cap-dependent translation [23,161,[181][182][183].…”
Section: Host Translationmentioning
confidence: 97%
See 1 more Smart Citation
“…This downregulation of IFITM proteins has already been shown to promote influenza virus A infection in HeLa cells and HFFs [180]. Interestingly, viruses employing internal ribosome entry sites (IRESs) for translation of their mRNAs may benefit from the inhibition of mTORC1, since those viruses do not depend on mTOR-driven cap-dependent translation [23,161,[181][182][183].…”
Section: Host Translationmentioning
confidence: 97%
“…T. gondii [177,178] Cleavage of mTOR via the protease GP63 in B10R macrophages to prevent IFN type I production and iNOS translation L. major [23] Mediates shut off of host translation which leads to a decreased translation of innate cytokines in U937 cells HSV-1 [179] Shut off of host translation to favor replication of own genome and to downregulate IFITM proteins Viruses relying on IRES-dependent translation [23,161,[180][181][182][183] Innate Cytokines…”
Section: Effect Pathogen Referencesmentioning
confidence: 99%
“…We speculate that some other signal pathways may be involved in and indispensable for PRRSV infection. Indeed, there have been a number of studies illustrating the relationship between PRRSV infection and mTOR signaling pathway (53), MyD88/ERK/AP-1 and NLRP3 inflammasome (54), ERK1/2-p-C/EBP-β Pathway (55) and Wnt/β-catenin pathway (56). Simultaneously deactivating the above-mentioned signal pathways probably will further block the PRRSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the PRRSV E protein did not significantly change the mRNA expression of GRP78 and GRP94 (data not shown), indicating that PRRSV E protein does not induce ER stress and subsequent degradation through the ERAD response. In addition, a previous study showed that PRRSV infection downregulated host protein expression by inducing host translation shutoff but UV-inactivated PRRSV did not (56). To test whether PRRSV E protein induces host translation shutoff, resulting in the degradation of pCH25H, we determined the levels of puromycin in 3D4/21 cells transfected with PRRSV E protein or cotransfected with PRRSV E protein and pCH25H.…”
Section: Discussionmentioning
confidence: 99%